2016
DOI: 10.4236/ojmm.2016.63017
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Bacterial Organisms Isolated from Cerebrospinal Fluid (CSF) of Children under Five Years in Windhoek from 2010 to 2014

Abstract: Bacterial meningitis (BM) is a life-threatening condition which affects the central nervous system (CNS). Its incidence rate is estimated between 0.22 -2.66 and 0.81 -6.1 cases/1000 lives worldwide and in Africa respectively. The objective of this study was to determine the frequency of bacterial organisms isolated from CSF of children less than five years old in Windhoek. A retrospective analysis was performed on 784 results of CSF submitted to the Namibia Institute of Pathology (NIP) from January 2010 to Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Our results revealed that Streptococcus pneumoniae (n = 14) followed by Haemophilus influenzae (n = 6) were the most prevalent bacteria detected in the CSF of ours under five years children hospitalized for meningitis, similar results has been reported in Namibia in 2013 [12], in Mozambique [13], in Kenya at Kenyatta Hospital where streptococcus pneumonia was about 51.2% [14]. A study done in Manhiça, a rural area in Southern Mozambique has reported Streptotoccus pneumoniae (n = 31) as the most prevalent bacteria in the CSF of children with meningitis followed by, Haemophilus influenzae (n = 13) and Open Journal of Pediatrics Neisseria meningitis (n = 8) [15].…”
Section: Discussionsupporting
confidence: 90%
“…Our results revealed that Streptococcus pneumoniae (n = 14) followed by Haemophilus influenzae (n = 6) were the most prevalent bacteria detected in the CSF of ours under five years children hospitalized for meningitis, similar results has been reported in Namibia in 2013 [12], in Mozambique [13], in Kenya at Kenyatta Hospital where streptococcus pneumonia was about 51.2% [14]. A study done in Manhiça, a rural area in Southern Mozambique has reported Streptotoccus pneumoniae (n = 31) as the most prevalent bacteria in the CSF of children with meningitis followed by, Haemophilus influenzae (n = 13) and Open Journal of Pediatrics Neisseria meningitis (n = 8) [15].…”
Section: Discussionsupporting
confidence: 90%